The effects of different postures and provocative swallow materials on the normative Chicago 3.0 metrics in a healthy Asian population - Mohd Said, Mohd Ridzuan; Wong, Zhiqin; Abdul Rani, Rafiz; Ngiu, Chai Soon; Raja Ali, Raja Affendi; Lee, Yeong Yeh (Blackwell Publishing, 2021)
Background and Aim: Variations in the Chicago 3.0 normative metrics may exist with different postures and with different provocative swallow materials in a healthy Asian population.